Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.tranon.2022.101346
|View full text |Cite
|
Sign up to set email alerts
|

Mo-MDSCs are pivotal players in colorectal cancer and may be associated with tumor recurrence after surgery

Abstract: Highlights Colorectal cancer patients present increased level of all MDSCs populations in peripheral blood. Eosinophilic MDSCs can be distinguished among PMN-MDSCs in the blood of colorectal cancer patients. In patients with colorectal cancer Mo-MDSCs correlate negatively with tumor antigen associated CD8+ T cells. In colorectal cancer patients an increase of circulating Mo-MDSCs after surgery may be associated with a higher risk of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…In patients with solid tumors, the number of MDSCs is positively correlated with cancer stage and tumor load [ 11 , 12 ] and is a biological marker of treatment failure as well as poor prognosis [ 13 15 ]. Under the joint regulation of the tumor microenvironment and tumor-derived factors secreted by cancer cells, MDSCs can be amplified and recruited to tumor primary and metastatic sites [ 16 , 17 ], while activated MDSCs can suppress the anti-tumor immune response of immune cells (e.g., NK cells, CD4 + T cells, and CD8 + T cells) through numerous mechanisms (e.g., the release of nitric oxide or reactive oxygen species [ 7 ], depletion of essential metabolites [ 8 ], induction of other immunosuppressive cells [ 9 ], and expression of negative immune checkpoint molecules [ 10 ]) in the tumor microenvironment, thus promoting tumor cells immune tolerance and leading to their immune escape.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with solid tumors, the number of MDSCs is positively correlated with cancer stage and tumor load [ 11 , 12 ] and is a biological marker of treatment failure as well as poor prognosis [ 13 15 ]. Under the joint regulation of the tumor microenvironment and tumor-derived factors secreted by cancer cells, MDSCs can be amplified and recruited to tumor primary and metastatic sites [ 16 , 17 ], while activated MDSCs can suppress the anti-tumor immune response of immune cells (e.g., NK cells, CD4 + T cells, and CD8 + T cells) through numerous mechanisms (e.g., the release of nitric oxide or reactive oxygen species [ 7 ], depletion of essential metabolites [ 8 ], induction of other immunosuppressive cells [ 9 ], and expression of negative immune checkpoint molecules [ 10 ]) in the tumor microenvironment, thus promoting tumor cells immune tolerance and leading to their immune escape.…”
Section: Introductionmentioning
confidence: 99%
“…MDSCs perform an important role in tumorigenesis and progression of cancer by primarily inhibiting T cell proliferation and activation via direct interaction, metabolic depletion, and cytokine modulation [ 35 , 60 , 61 ]. For instance, M-MDSCs significantly promote the activation of dormant micro-metastatic cells compared to PMN-MDSCs [ 62 , 63 ]. In acute myeloid leukemia (AML), elevated M-MDSC count is significantly associated with poor prognosis [ 64 ].…”
Section: Monocytes and Monocyte-derived Cells In Tumorigenesismentioning
confidence: 99%
“…In metastatic CRC, it was found that high numbers of G-MDSC were associated with poor prognosis [ 60 ]. Moreover, levels of circulating M-MDSCs were significantly elevated in most advanced tumor stages of CRC patients [ 66 ]. Additionally, levels of circulating M-MDSCs were significantly elevated after surgery, indicating that M-MDSCs levels are related to disease burden and tumor recurrence [ 66 ].…”
Section: Prognostic Significance Of Mdscs In Crcmentioning
confidence: 99%
“…Moreover, levels of circulating M-MDSCs were significantly elevated in most advanced tumor stages of CRC patients [ 66 ]. Additionally, levels of circulating M-MDSCs were significantly elevated after surgery, indicating that M-MDSCs levels are related to disease burden and tumor recurrence [ 66 ]. Similarly, expansion of circulating G-MDSCs was found to be correlated with higher stage and histological grade of malignancy, indicating their role in cancer progression [ 48 ].…”
Section: Prognostic Significance Of Mdscs In Crcmentioning
confidence: 99%